2011
DOI: 10.17221/1564-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Progressive rod-cone degeneration (PRCD) in selected dog breeds and variability in its phenotypic expression

Abstract: Progressive rod-cone degeneration (PRCD) is a late onset autosomal photoreceptor degeneration found in canines. PRCD in canines is homologous to one form of retinitis pigmentosa (RP) found in humans and displays phenotypic similarity as well as having the identical causative mutation. The PRCD gene was mapped to the centromeric region of canine chromosome 9 (CFA9). We report here a population study of 699 dogs of the following breeds and the following frequencies of the disease-causing mutation: American Cocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
0
16
1
Order By: Relevance
“…photoreceptor | PRCD | retinal degeneration | microglia P rogressive rod-cone degeneration (PRCD) is a canine retinal disease and the most common known cause of blindness in dogs, affecting over 35 breeds with allelic frequency as high as 45% (1)(2)(3)(4)(5). The disease is caused by a single C2Y mutation in the Prcd gene, which is expressed specifically in the retina (6,7).…”
mentioning
confidence: 99%
“…photoreceptor | PRCD | retinal degeneration | microglia P rogressive rod-cone degeneration (PRCD) is a canine retinal disease and the most common known cause of blindness in dogs, affecting over 35 breeds with allelic frequency as high as 45% (1)(2)(3)(4)(5). The disease is caused by a single C2Y mutation in the Prcd gene, which is expressed specifically in the retina (6,7).…”
mentioning
confidence: 99%
“…It has been reported that ECS are affected by a relatively late onset and slowly progressive form of PRA, as demonstrated by late changes on funduscopy, areas of delayed retinal degeneration on histology and delayed loss of the b‐wave function on ERG in comparison to other breeds . There is a relatively high prevalence of prcd mutations in this breed, which is a late‐onset form of PRA . In the present study, all of the dogs included were ECS which is a very popular breed in the United Kingdom and one of the most common dog breeds presented to the RVC during the period of the study.…”
Section: Discussionmentioning
confidence: 80%
“…17,19 There is a relatively high prevalence of prcd mutations in this breed, which is a late-onset form of PRA. 16,21 In the present study, all of the dogs included were ECS which is a very popular breed in the United Kingdom and one of the most common dog breeds presented to the RVC during the period of the study. When counseling the owners, it was discussed that the visual outcome and how long the dog could remain visual post-surgery were unknown at the time.…”
Section: Discussionmentioning
confidence: 99%
“…They are one of the >60 breeds of dogs that carry the mutation in PRCD resulting in a late-onset PRA within the breed. 4,11,12 The genetic test for PRCD has been available to the SWD breeders for over 10 years, and it has been utilized to aid in breeding programs to remove the mutation from the SWD population (swdclub.org).…”
Section: Discussionmentioning
confidence: 99%